Over-winter persistence of supraglacial lakes on the Greenland Ice Sheet: results and insights from a new model. Issue 257 (18th June 2020) - Law, Robert; Arnold, Neil; Benedek, Corinne; Tedesco, Marco; Banwell, Alison; Willis, Ian
Abstract: We present a newly developed 1-D numerical energy-balance and phase transition supraglacial lake model: GlacierLake. GlacierLake incorporates snowfall, in situ snow and ice melt, incoming water from the surrounding catchment, ice lid formation, basal freeze-up and thermal stratification. Snow cover and temperature are varied to test lake development through winter and the maximum lid thickness is recorded. Average wintertime temperatures of −2 to $-30^{° }{\rm C}$ and total snowfall of 0 to 3.45 m lead to a range of the maximum lid thickness from 1.2 to 2.8 m after ${\sim }250$ days, with snow cover exerting the dominant control. An initial ice temperature of $-15^{° }{\rm C}$ with simulated advection of cold ice from upstream results in 0.6 m of basal freeze-up. This suggests that lakes with water depths above 1.3 to 3.4 m (dependent on winter snowfall and temperature) upon lid formation will persist through winter. These buried lakes can provide a sizeable water store at the start of the melt season, expedite future lake formation and warm underlying ice even in winter.